464 ESCALATION DURING COVID-19. (14th June 2021) - Magee, M
Abstract: Introduction: During the first surge of COVID-19 it was well recognised that early identification of a plan for escalation in the event of deterioration for each patient was vital. If no decision is documented it results in junior staff frequently making decisions regarding escalation in the out of hours period. This leads to patients, or family members, having these conversations with a doctor they may never have met before. My aim was to improve the documentation of escalation plans in all patients within the first 24 hrs of admission. Method: Baseline data was collected in September 2019 with further samples in April 2020 and August 2020. Patient medical notes were reviewed to identify if an escalation plan had been made during the period from admission to post take ward round. A COVID admission pathway document was introduced with a specific section on Clinical Frailty Score and Escalation plan between the baseline and April 2020 data. Results: Baseline data showed that only 12.8% of medical patients had a documented escalation plan within the first 24 hrs of admission to hospital. During the first surge in April 2020 this number had improved to 47% following introduction of the COVID-19 admission pathway. This included 100% of patients admitted to respiratory wards. Unfortunately when reassessed in August 2020, this number had fallen to 16%. Conclusion: Introduction of clinical frailty scoring and an area specifically to document escalation discussions resulted in a marked improvement. Heightened awareness of rapid deterioration of patients during the first surge almost certainly played a role in this. Unfortunately this was not sustained once staff discontinued the use of COVID-19 admission document. Moving forward we will incorporate these sections into the medical and surgical admissions pathways in the hope it produces similar results.